Gobierno abierto: una concepción ética para la educación democrática - Pallarés Domínguez, Daniel (Revista del CLAD Reforma y Democracia, 2019)
AbstractThe notion of open government has been established in representative democracies since the 70s of the XXst century. However, the greater access to public and political information by civil society has been applied asymmetrically, placing great emphasis on the legal framework but little on the moral framework. This study aims to analyse the conception of open government and its main problems from a political and philosophical point of view. Among these we highlight some contradictions in the laws of transparency in the Spanish and European panorama; the type of information that is transmitted; and the conception of civil society that should promote a greater culture of transparency in an ethical sense.
Keywords: Gobierno Abierto; Participación Ciudadana; Democracia; Transparencia; Sociedad Civil; Ética